Towards Discursive Justice: An Integrative Foucault-Islam Framework for Critical Media Discourse Analysis in Justice Issues - Qudratullah, Qudratullah; Nohong, Mursalim; Iqbal, Muhamad; Susanti, Ressi; Alkanan, Omer Mohamed Taha (Jurnal Ilmiah Al-Syir'ah, 2025)
This research aims to analyze the construction of online media discourse in the "Vina Cirebon" case through the integration of Foucauldian discourse analysis and Islamic legal perspectives to understand the dynamics of power, knowledge, and justice in media narratives. Using a qualitative approach with case study design, this research analyzes six Kompas.com news articles from January-June 2024 selected purposively. The analytical method includes critical discourse analysis based on Foucault's model examining knowledge systems, power-knowledge relations, regimes of truth, and subject construction, which is then evaluated using Islamic legal perspectives on principles of justice (al-’adl), transparency (al-wuduh), and protection of human dignity (karamah al-insan). Research findings reveal that media operates as a discursive apparatus legitimizing institutional dominance of the Indonesian National Police (POLRI) in controlling information production and distribution, where "truth" is constructed through discursive practices that marginalize alternative perspectives. Islamic legal evaluation shows misalignment between media practices and Islamic justice principles, particularly in transparency and protection of individual dignity. This research produces the innovative concept of "discursive justice" that demands media practices to be not only procedurally fair but also substantively protective of human rights. The findings indicate the need for transformation of the media ecosystem towards more responsible and ethical practices in the context of justice.